Integration of the antennal lobe glomeruli and three projection neurons in the standard brain atlas of the moth Heliothis virescens - Løfaldli, Bjarte B.; Kvello, Pål; Mustaparta, Hanna (Frontiers in Systems Neuroscience, 2010)
Digital three dimensional standard brain atlases are valuable tools for integrating neuroimaging data of different preparations. In insects, standard brain atlases of five species are available, including the atlas of the female Heliothis virescens moth brain. Like for the other species, the antennal lobes of the moth brain atlas were integrated as one material identity without internal structures. Different from the others, the H. virescens standard brain atlas exclusively included the glomerular layer of the antennal lobe. This was an advantage in the present study for performing a direct registration of the glomerular layer of individual preparations into the standard brain. We here present the H. virescens female standard brain atlas with a new model of the antennal lobe glomeruli integrated into the atlas, i.e. with each of the 66 glomeruli identified and labelled with a specific number. The new model differs from the previous H. virescens antennal lobe model both in respect to the number of glomeruli and the numbering system; the latter according to the system used for the antennal lobe atlases of two other heliothine species. For identifying female specific glomeruli comparison with the male antennal lobe was necessary. This required a new male antennal lobe atlas, included in this paper. As demonstrated by the integration of three antennal lobe projection neurons of different preparations, the new standard brain atlas with the integrated glomruli is a helpful tool for determining the glomeruli innervated as well as the relative position of the axonal projections in the protocerebrum.